Prevention is Primary : Strategies For Community Well Being - Editors Cohen, Larry, 1947 May 21- ; Chávez, Vivian and Chehimi, Sana (San Francisco Jossey-Bass, 2010)
The new edition of Prevention Is Primary provides models, methods, and approaches for building health and equity in communities. This comprehensive book includes the theory, concepts, and models needed to harness social justice and practice primary prevention of unnecessary illness and injury. Ideal for students as well as practitioners, this thoroughly revised and updated second edition combines an overview of advances in the field with effective approaches in the current economic and health care climate. With contributions from noted experts, Prevention Is Primary shows practical applications of intervention science to social and health problems and issues facing at-risk and vulnerable groups. The book describes the overarching framework and principles guiding prevention efforts, including a focus on social justice and health equity, and community resilience. It explores the transition from prevention theory to implementation and practice and from interdisciplinary collaboration to evaluation. Highlighting the book's usefulness as a teaching and learning tool, Prevention Is Primary has real world examples, learning objectives, and review questions for each chapter.
Include Index
Keywords: Medical policy -- Medicine, Preventive -- Social medicine